An Evaluation of an Integrated Disaster Management and an Emergency Assembly Area: The Case of Kadikoy, Istanbul - Bektas, Yasin; Sakarya, Adem (KONYA TECHNICAL UNIV, FAC ARCHITECTURE & DESIGN, 2020)
Purpose The present study aims to analyze the accessibility and adequacy of the emergency assembly areas (EAAs) in Kadikoy which has the highest ratio of at-risk buildings in Istanbul. Design/Methodology/Approach In this study, accessibility and adequacy of the EAAs are analyzed. To analyze the accessibility network analysis carried out within a geographic information system (GIS) program is used. Through an accessibility analysis, the ratio of the population that resides within 500 m walking distance of each EEA was ascertained. Furthermore, an adequacy analysis was carried out to measure the size of each emergency assembly area, and its adequacy for the population within its catchment area was analyzed. In addition, an accessibility and adequacy analysis were made of the social infrastructure facilities that have been defined as second-level emergency assembly areas. Findings According to the research findings, 57 percent of the current population of the district resides within 500 m of one or more of Kachkoy's 73 EEAs. It was found also that the emergency assembly areas accessible by three-quarters of the population within 500 m could be considered inadequate. Based on these findings, it was concluded that emergency assembly areas should be of adequate size, away from disaster risks and accessible to all residents, and that the standards for the open and closed areas within the emergency assembly areas should be defined in legislation and included as mandatory in future plans. Research Limitations/Implications The research was limited to Kadikoy which has the highest ratio of at-risk buildings in Istanbul. Originality/Value When evaluated alongside relevant studies regarding EAAs, the present study can be said to contribute to literature in its analysis of both the accessibility and adequacy of the existing EAAs and secondary assembly areas, taking a holistic approach, the study makes use of a network analysis method in the GIS program to identify the number of people living in each residential structure within the Kadikoy district. In addition, the study seeks to contribute further to literature by measuring the accessibility of social and technical infrastructure within the city planning discipline through a network analysis.
Keywords: Disaster risk; emergency assembly area; integrated disaster management; network analysis; urban planning; GIS; Architecture